2014
DOI: 10.1371/journal.pone.0086354
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine Ameliorates Dopamine-Releasing Deficits and Behavioral Deficits in Rats after Fluid Percussion Injury

Abstract: AimsTo investigate the role of dopamine in cognitive and motor learning skill deficits after a traumatic brain injury (TBI), we investigated dopamine release and behavioral changes at a series of time points after fluid percussion injury, and explored the potential of amantadine hydrochloride as a chronic treatment to provide behavioral recovery.Materials and MethodsIn this study, we sequentially investigated dopamine release at the striatum and behavioral changes at 1, 2, 4, 6, and 8 weeks after fluid percuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…Moreover, DA metabolites (DOPAC and HAV) increased significantly in the amantadine-treated rats at this time point, which may be associated with residual DA neurons hyperfunction and increased DA release metabolism [53]. The transient increase of DA at the subacute phase (1-2 weeks after surgery) may result from the spontaneous regrowth of DAergic fibers [54,55] and decreased dopamine transporters (DAT) which play a key role in extracellular DA reuptake [51,56]. Our study revealed that post-TBI depression may be related to the dopaminergic concentration in the striatum, and hence preserving the normal concentration level may be a potential target for post-TBI depression therapy [Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, DA metabolites (DOPAC and HAV) increased significantly in the amantadine-treated rats at this time point, which may be associated with residual DA neurons hyperfunction and increased DA release metabolism [53]. The transient increase of DA at the subacute phase (1-2 weeks after surgery) may result from the spontaneous regrowth of DAergic fibers [54,55] and decreased dopamine transporters (DAT) which play a key role in extracellular DA reuptake [51,56]. Our study revealed that post-TBI depression may be related to the dopaminergic concentration in the striatum, and hence preserving the normal concentration level may be a potential target for post-TBI depression therapy [Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Several of these drugs show promise in reducing chronic signaling deficits following injury, such as increasing DA levels in the striatum and substantia nigra while also reducing neuronal death ( Zhu et al , 2000 ; Wagner et al , 2008 , 2009 ; Rau et al , 2012 ; Huang et al , 2014a , 2014b ; Wang et al , 2014 ; Tan et al , 2015 ; Phelps et al , 2017 ). In turn, performance is improved acutely for TBI animals on traditional tasks for assessing cognitive deficits, such as the MWM and novel-object recognition tasks, following administration of such therapeutic agents ( Zhu et al , 2000 ; Wagner et al , 2008 , 2009 ; Rau et al , 2012 ; Huang et al , 2014a , 2014b ; Wang et al , 2014 ; Tan et al , 2015 ; Leary et al , 2017 ; Phelps et al , 2017 ). At the same time, pharmacotherapies that reduce DA signaling, such as haloperidol and resperidone, exacerbate acute MWM deficits, in both TBI and non-TBI animals ( Wilson and Hamm, 2002 ; Kline et al , 2007 , 2008 ; Hoffman et al , 2008 ), giving support for a significant contribution of reduced DA signaling in cognitive dysfunction.…”
Section: Special Considerations For Pharmacotherapy Following Traumatmentioning
confidence: 99%
“…Pramipexole has neuroprotective effect against glutamate-induced neurotoxicity [84]. Amantadine leads to recovery and decreases dopamine-release deficits in TBI patients [85,86]. Chronic use of benzodiazepines offers no neuroprotection while immediate administration after ischemia is neuroprotective [87].…”
Section: Pramipexole Amantadine Benzodiazepines Trazodonementioning
confidence: 99%